Emotional Interlligence why it can matter more then IQ - Goleman, Daniel (Bloomsbury, 1996)
"Counter Everyone knows that high IQ is no guarantee of success, happiness, or virtue, but until the discoveries of modern brain researchers, theorists could only guess why. Daniel Goleman's fascinating report from the frontiers of psychology and neuroscience offers us startling new insight into our "two minds" -- the rational and the emotional -- and how they together shape our destiny. Beginning deep in the brain, Emotional Intelligence shows us the exact mechanism of an "emotional hijack," when passion overcomes reason. Through vivid examples, Goleman then delineates the crucial skills of emotional intelligence, and shows how they determine our success in relationships and work, and even our physical well-being. What emerges is a crucial new way to talk about being smart. The final chapters reveal the possibilities -- and limits -- of "emotional literary," as it is taught by both parents and educators. The book concludes with a compelling vision of what true emotional intelligence means for us both as individuals and as a society. The message of this eye-opening book is one we must take to heart: the true "bell curve" for a democracy must measure emotional intelligence. Daniel Goleman offers a new vision of excellence and a vital new curriculum for life that can change the future for us and our children." http://www.loc.gov/catdir/description/random0413/95016685.html.